Flow semantics for intellectual control in IoT systems. Issue 2 (3rd April 2018) - Linger, Richard C.; Hevner, Alan R.
ABSTRACT: Effective decision making is critical for operation and control of Internet of Things (IoT) systems. These systems are comprised of massive numbers of hardware, software and network components; all sensing, computing, communicating and controlling in dynamic architectures and state spaces of extraordinary complexity. Components, connections and users will come and go, quality and reliability will be unpredictable, and failures and intrusions will be ever-present. It is vital that these systems be rigorously designed, developed, and governed; but how can a rigorous engineering discipline be defined for an environment where the capability, connectivity, and integrity of components will vary from moment to moment? In this paper, we focus on Flow Semantics as a rigorous engineering foundation for analysis, development, evolution, operation, and governance of IoT systems in such unpredictable environments. The research goal is to develop engineering principles and practices for maintaining intellectual control in IoT systems for effective decision-making.